2019
DOI: 10.1302/0301-620x.101b9.bjj-2018-1096.r1
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid or epsilon-aminocaproic acid in total joint arthroplasty? A randomized controlled trial

Abstract: Aims Antifibrinolytic agents, including tranexamic acid (TXA) and epsilon-aminocaproic acid (EACA), have been shown to be safe and effective for decreasing perioperative blood loss and transfusion following total hip arthroplasty (THA) and total knee arthroplasty (TKA). However, there are few prospective studies that directly compare these agents. The purpose of this study was to compare the benefits of intraoperative intravenous TXA with EACA. Patients and Methods A total of 235 patients (90 THA and 145 TKA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
1
39
0
1
Order By: Relevance
“…These results are consistent with previous studies. 13,14 The pooled results indicated that the Hb levels at discharge in the EACA group were similar to those in the TXA group. The indications for blood transfusion were based on postoperative Hb levels and clinical symptoms of anemia.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These results are consistent with previous studies. 13,14 The pooled results indicated that the Hb levels at discharge in the EACA group were similar to those in the TXA group. The indications for blood transfusion were based on postoperative Hb levels and clinical symptoms of anemia.…”
Section: Discussionmentioning
confidence: 78%
“…No additional studies were obtained after reviewing the references. Ultimately, three RCTs and three non-RCTs [7][8][9][10]13,14 were eligible for data extraction and the meta-analysis. The search process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…As the safety of intramuscular and oral regimens has not been supported by a large number of clinical trials, these methods were excluded from this study. Some scholars have suggested that when TXA is used topically in the joint cavity, joint cavity drainage must not be placed after surgery, to avoid loss of drug efficacy 23,24 . Therefore, to reduce the bias in the test results, a temporary clamping scheme for the drainage tube for 4 h after operation was used in this study 11,25 .…”
Section: Discussionmentioning
confidence: 99%
“…As the safety of intramuscular and oral regimens has not been supported by a large number of clinical trials, these methods were excluded from this study. Some scholars have suggested that when TXA is used topically in the joint cavity, joint cavity drainage must not be placed after surgery, to avoid loss of drug e cacy 23,24 . Therefore, to reduce the bias in the test results, a temporary clamping scheme for the drainage tube for 4 h after operation was used in this study 11,25 .…”
Section: Discussionmentioning
confidence: 99%